(untitled) - Jackson, Dunham (Mineola, N.Y., 1941)
The underlying theme of this monograph is that the fundamental simplicity of properties of orthogonal functions and the developments in series associated with them not only commends them to the attention of the student of pure mathematics, but also renders them inevitably important in the analysis of natural phenomena which lend themselves to mathematical description.
Keywords: Orthogonal polynomials,Đa thức Orthogonal